Capital inflows, sustained investment surges, and the role of external economies of scale in a developing economy - Arslan Razmi (University of Massachusetts, Department of Economics, 2019)
Standard open economy macro models with unemployment predict a contractionary short-run effect of international capital inflows. Empirical evidence, on the other hand, often associates such inflows with short-term booms, and developing country policy makers frequently go out of their way to welcome foreign capital. Employing a portfolio balance framework, this paper distinguishes between international financial (i.e., bond) and "real" (i.e., equity) flows to explore the different consequences for capital accumulation that may follow over the medium run. The presence of external economies of scale generates multiple equilibria, and different kinds of capital flows may push investment in one direction or the other for sustained periods of time.
Keywords: F21; F32; F43; O11; 330; Capital flows; economies of scale; investment surges; realexchange rate